Exploring the potential of Ricinodendron heudelotii and anarcadium occidentale (Cashew nut) oil quality and purity from Ivory Coast - Soro, Kili Frederique Djolaud; Boukachabine, Khadija; El-Antari, Abderraouf (International Journal of Sustainable Agricultural Research, 2025)
This study aimed to characterize and compare oils extracted from the seeds of Ricinodendron heudelotii and Anacardium occidentale, two underexploited oilseed species from Côte d’Ivoire, to evaluate their potential for local valorization and sustainable use. Seeds were collected from different producing regions, and oil extraction was performed using the Soxhlet method. Lipid yield, oil quality parameters (free acidity, peroxide value, K232, K270), fatty acid composition, minor constituents (sterols, tocopherols), and physical properties (color, viscosity) were assessed. Results showed that the acidity index of both oils complied with Codex Alimentarius standards (≤ 4.0 mg KOH/g oil). Anacardium occidentale oil exhibited good oxidative stability, with peroxide values ranging from 1.2 to 8.8 meq O2/kg, whereas Ricinodendron heudelotii oil showed higher values (38–64 meq O2/kg), reflecting compositional differences. Fatty acid analysis revealed a predominance of oleic acid (65%) in A. occidentale oil, known for cardiovascular benefits, while R. heudelotii oil was rich in nervonic acid (49–54%), a fatty acid with functional applications. Both oils contained high β-sitosterol (>80%), and R. heudelotii oil exhibited notably high tocopherol content (480–1140 mg/kg). Overall, these findings highlight the complementary properties of the two oils. Their valorization could strengthen local oilseed value chains, reduce dependence on imported vegetable oils, and support sustainable development and nutritional security in Côte d’Ivoire. Vegetable oils; Oilseed seeds; Quality parameters; Fatty acid profile; Tocopherols; Sterols; Ricinodendron heudelotii; Anacardium occidentale; Côte d’Ivoire.